2008
DOI: 10.1093/aje/kwn308
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age and Infant Mortality: A Test of the Wilcox-Russell Hypothesis

Abstract: It has been argued (e.g., the Wilcox-Russell hypothesis) that (low) birth weight is a correlate of adverse birth outcomes but is not on the “causal” pathway to infant mortality. However, the US national policy for reducing infant mortality is to reduce low birth weight. If these theoretical views are correct, lowering the rate of low birth weight may have little effect on infant mortality. In this paper, the authors use the “covariate density defined mixture of logistic regressions” method to formally test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
2
16
0
2
Order By: Relevance
“…Regarding maternal factors affecting child mortality, the total fertility rate of 6-7 in Uganda is very high, 42 and child-spacing is often limited. Although low birthweight contributes to infant deaths 43,44 and is more common in teenage mothers, [45][46][47] no significant association between child mortality and teenage births was found. As in other studies, 48-51 slightly higher death rates were observed in children born to women in their 40s than in those with younger mothers, although, because the sample size of mothers over 40 was relatively small, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding maternal factors affecting child mortality, the total fertility rate of 6-7 in Uganda is very high, 42 and child-spacing is often limited. Although low birthweight contributes to infant deaths 43,44 and is more common in teenage mothers, [45][46][47] no significant association between child mortality and teenage births was found. As in other studies, 48-51 slightly higher death rates were observed in children born to women in their 40s than in those with younger mothers, although, because the sample size of mothers over 40 was relatively small, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A statistical method of examining the causal role of birth weight, within the context of the proximate determinants model, has been developed (Gage et al 2004, 2009), based on the Wilcox-Russell definition of “causality” (Wilcox and Russell 1990). The aim of this research is to determine whether maternal education, as a measure of socioeconomic level, affects infant mortality indirectly (though birth weight), directly (independent of birth weight), or both.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent mothers and their babies have less prenatal care, more health problems, and more hospital admission 22. In general, mothers between 25-35-years-of-age are more likely to have healthier babies who display more appropriate GA-related birth weight and lower mortality rate 23. It is not clear why maternal age is an influential factor on salivary cortisol level in infants.…”
Section: Discussionmentioning
confidence: 99%